'Not a cure, but helpful' – exploring the suitability of evidence-based psychological interventions to the needs of Black, Asian and Minority Ethnic (BAME) communities. (11th January 2023) - Faheem, Afsana
Abstract: Individuals from Black, Asian and Minority Ethnic (BAME) groups experience profound disparities in accessing mental healthcare, show poorer treatment outcomes, and high attrition rates when compared to their White British counterparts. Despite the national rollout of Improving Access to Psychological Therapies (IAPT) services, research exploring service users' recovery narrative has been scarce. The aim of this study was to explore whether evidence-based psychological interventions are suitable to the needs of BAME communities. Semi-structured interviews were conducted with nine BAME service users who received evidence-based psychological treatment(s) from IAPT services. Reflexive thematic analysis (RTA) was used to analyse the data which included a six-phase process to produce a robust pattern-based analysis. Overall, three themes were generated. The first theme highlighted the importance of recognising cultural dissonance within therapy, which considered patient therapeutic expectations, therapeutic guilt, and conflicting cultural identities. The second theme identified the need for therapists to develop cultural competency. This included the importance of building therapeutic trust and exploration of patient culture within therapy. The final theme considered the road to recovery and highlighted challenges with therapeutic engagement and evaluations of therapeutic effectiveness. Overall, BAME service users felt that therapy was not a cure, but found it helpful. Clinical implications and future recommendations are discussed. Key learning aims: (1) To briefly introduce cross-cultural theoretical models that may assist mental health professionals to think critically about whether Western notions of therapy are suited to the needs of ethnic minority communities. (2) To highlight cultural challenges that may impede therapeutic success for BAME communities. (3) For IAPT services and practitioners to consider cultural competency training needs that may enhance service user therapeutic experiences and outcomes. (4) To encourage IAPT services to enhance knowledge about psychotherapy and mental health by promoting culturally sensitive psychoeducation in ethnic minority communities.